Board characteristics and Bank Performance: Which factor is more important? - Lee-Anne C Johennesse; I Gusti Agung Musa Budidarma Budidarma (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study seeks to find the rank of corporate governance characteristics that affect bank performance. The artificial neural network is employed in the analysis instead of regression analysis. There are two dependent variables which are ROA and PER that represents the accounting performance and the market performance. Size of the board of directors, gender diversity of the board, and board independence are the corporate governance characteristics considered in this study. Board independence is the most important factor in determining both accounting performance and market performance. However, the size of the board of directors becomes the second-factor affecting a bank’s accounting performance and the last factor affecting the bank’s market performance, while gender diversity is the last factor for accounting performance and the second factor for market performance.